COMPLETION OF THE TRANSPORTATION PROBLEM WITH USING PASCAL-BASED NORTHWEST CORNER - Dian Novita Lestari; Haryanto Haryanto, SKom, MM (Jurnal Sistem Informasi, 2002)
Transportation problem can be solved by using the method of the Northwest Corneras the initial solution and multiplier methods for test optimization. Northwest Cornermethod is the simplest method among the methods among others to seek earlysolution. The drawback is this method not consider the per-unit transport costs inmaking the allocations, so we need some additional solution iterations before theoptimum solution obtained. But it can happen although rare, where the solution beginthe same or better can be achieved through this method. However, after using themultiplier method of transportation problems can achieve an optimum solution.